Factors associated with returning to work in head and neck cancer survivors in Singapore: A preliminary exploratory mixed‐methods approach study. Issue 5 (18th February 2021) - Rangabashyam, Mahalakshmi; Koh, Shu Qing; Sultana, Rehena; Tan, Ngian Chye; Iyer, N. Gopalakrishna; Soo, Khee Chee; Fenwick, Eva; Lamoureux, Ecosse; Tan, Hiang Khoon
Abstract: Background: Little is known about return‐to‐work (RTW) among Asian head and neck cancer (HNC) survivors. We investigated the prevalence and factors associated with RTW among HNC patients with in Singapore. Methods: In this cross‐sectional mixed‐methods study, 80 HNC patients, who had been working prior to diagnosis, completed questionnaires and 15 participated in qualitative interviews to explore perceived barriers and facilitators of RTW. Multivariate logistic regression was used to evaluate factors associated with not‐returning‐to‐work (NRTW) within 6 months of treatment completion. Results: Thirty‐five participants reported NRTW 43.8%. Multivariable analysis showed that patients with advanced stage (III‐IV) cancer (odds ratios [OR] = 4.51, 95% confidence intervals [CI]: 1.15–13.28, p = 0.006), multi‐modality treatment (OR = 4.62, 95% CI: 1.38–15.52, p = 0.013), and pink‐collar jobs (OR = 9.30, 95% CI: 1.70–50.83, p = 0.010) had higher odds of NRTW. Conclusion: The factors associated with employment after HNC treatment are complex. Identification of key modifiable factors may lead to improved RTW outcomes.